(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This research aims to study the effectiveness of efforts and legislation taken to combat rumors on social media and their impact on the intellectual security of Saudi youth. A sample of 200 Saudi youth was used to analyze their answers to several paragraphs related to the impact of rumors and intellectual security, in addition to the effectiveness of efforts and legislation in combating this phenomenon. The results showed that most of the sample members agree on the importance of legislation and laws to combat rumors on social media platforms. The paragraphs related to criminalizing the transmission of information without verifying its accuracy, and imposing fines and penalties on rumor mongers, recorded high levels of positive responses. The results also showed support for the idea of ​​establishing media and research centers to monitor rumors and measure public opinion, in addition to the importance of spreading continuous awareness about the dangers of rumors. The results of the analysis of the relationship between rumors and intellectual security indicate a strong relationship between the impact of rumors on social media platforms and intellectual security among Saudi youth, as the results of the Pearson test showed a strong positive correlation (correlation coefficient 0.712), indicating that the increase in the impact of rumors is associated with the deterioration of intellectual security. The results also showed a moderate relationship between the rate of youth exposure to rumors and their impact on intellectual security. In light of these results, the study recommends several measures to strengthen the fight against rumors, such as organizing ongoing awareness campaigns in schools and universities to teach youth how to verify the accuracy of information. It also stresses the need to enhance critical thinking among youth by introducing these skills into curricula. On the other hand, it is recommended that the government sector cooperate with social media platforms to develop tools to monitor rumors, and develop deterrent laws and legislation to combat fake news.